Differences in osmotolerant and cell-wall properties of two Zygosaccharomyces rouxii strains - Pribylová, L; Farkas, V; Slaninová, I; de Montigny, J; Sychrová, H (Folia microbiologica, 2007)
The osmotolerant and cell wall properties of the two most studied wild-type Zygosaccharomyces rouxii strains (CBS 732 and ATCC 42981) were examined. Differences in their (1) tolerance to high salt content in the medium, (2) resistance to the lysing enzymes Lyticase and Zymolyase, (3) cell-wall polymer content and (4) cell wall micromorphology suggested that the less osmotolerant CBS 732 strain possesses a more rigid cell wall than the more osmotolerant ATCC 42981, whose cell wall seems to be more flexible and elastic.
Keywords: osmolární koncentrace; Saccharomyces cerevisiae; fyziologická adaptace; Zygosaccharomyces; buněčná stěna; Multienzyme Complexes; Glucan Endo-1,3-beta-D-Glucosidase; Osmolar Concentration; endo-1,3-beta-glukanasa; Antifungal Agents; Saline Solution, Hypertonic; proteasy; Peptide Hydrolases; Cell Wall; antifungální látky; multienzymové komplexy; hypertonický solný roztok; Adaptation, Physiological